Mamadeira e aleitamento materno como fatores de risco para cárie dentária na dentição decídua: revisão sistemática e meta análise - Walesca de Melo Avila (2015)
Studies of the role of breastfeeding and bottle feeding in the occurrence of dental caries during childhood are important to help dentists and parents prevent caries, and also for the creation of public health policies. However, no consensus has yet been reached in literature regarding the issue. The aim of the present systematic review and meta-analysis was to seek scientific evidence relating to the clinical question: Do bottle fed children have more dental caries in primary dentition than children that were breastfed? Seven electronic databases and grey literature were searched. Two independent reviewers selected the studies, extracted data and evaluated risk of bias by quality assessment. Meta-analysis was conducted and the summary risk measure (odds ratio-OR) and 95% confidence intervals (95%CI) were calculated. Seven studies were included in the review: five cross-sectional, one case-control and one cohort study. Meta-analysis of the four cross-sectional studies did not reveal a statistically significant association between dental caries and whether the child was breast or bottle fed (OR: 1.16; 95%CI: 0.60-2.23). Four studies showed that bottle fed children had more dental caries than breast fed children (p<0.05), while three studies did not find an association (p>0.05). Scientific evidence regarding the role of breastfeeding and bottle feeding in the occurrence of dental caries during childhood is weak. Until new evidence is found, breastfeeding is recommended until up to six months of age, due to the fact that it has major benefits for the systematic health of babies. Further prospective observational cohort studies are needed to obtain new evidence.